1992
DOI: 10.1039/dt9920002145
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein cross-reactions involving plastocyanin, cytochrome f and azurin: self-exchange rate constants and related studies with inorganic complexes

Abstract: Protein-protein cross-reactions involving acidic and basic plastocyanins, cytochrome f and azurin, and including reactions between t w o blue copper proteins, have been studied for the first time. The high reactivity of cytochrome f, and properties of the basic Anabaena variabilis plastocyanin, are noted. Reduction potentials for different plastocyanins have been obtained at p H 7-9 and are in the range 340-380 mV. The application of Marcus theory has enabled self-exchange rate constants (25 "C) for acidic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…5). At the lower pH values, the behavior is similar to that observed for plastocyanin (23)(24)(25) and is attributed to the acid-base properties of an active-site histidine of the Cu(I) protein. From the difference between the pK a values for amino acid residues in the two oxidation states of the protein, it is possible to determine, using Equation 1, the effect of protonation or deprotonation of specific amino acid residues on the redox potential of the protein (26):…”
Section: Resultssupporting
confidence: 53%
“…5). At the lower pH values, the behavior is similar to that observed for plastocyanin (23)(24)(25) and is attributed to the acid-base properties of an active-site histidine of the Cu(I) protein. From the difference between the pK a values for amino acid residues in the two oxidation states of the protein, it is possible to determine, using Equation 1, the effect of protonation or deprotonation of specific amino acid residues on the redox potential of the protein (26):…”
Section: Resultssupporting
confidence: 53%
“…The unique spectroscopic properties of blue copper include an LMCT [S(Cys) → Cu 2+ ] absorption at ∼600 nm (ε ∼ 4700 M -1 cm -1 ) and a narrow parallel hyperfine EPR splitting pattern. Plastocyanins have relatively high reduction potentials (340−370 mV vs NHE at pH 7) . The small Cu 2+/+ nuclear reorganization energy and the covalent nature of the Cu−S(Cys) bond facilitate long-range ET reactions with donor and acceptor molecules. , …”
Section: Introductionmentioning
confidence: 99%
“…Figure , reproduced from ref , illustrates the variation in reversible potentials for several plastocyanins under a range of chemical redox conditions. The voltammetric data obtained in the present work, like the data in Figure , also show that positively charged A. variabilis plastocyanin has a considerably more positive E ° f value than any of the negatively charged plastocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…Antecedent Redox Studies on Plastocyanins. Detailed redox studies on plant plastocyanins by chemical and electrochemical techniques have been reported. Using rate data derived from chemical redox reactions, Sykes et al. concluded that A. variabilis plastocyanin has a less positive E ° f value than the plastocyanins from two plants (parsley and spinach) and another alga ( Scenedesmus obliquus ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation